Bioprospecção de Syagrus cocoides Martius em modelo experimental de desordem isquêmica cardíaca induzida em ratos - PENHA, Ellen Caroline Da Silva (2023)
Cardiovascular diseases (CVD) constitute a global health problem, responsible for more than 17 million deaths annually, being the main cause of death, in particular, ischemic heart disease (IHD) is the most prevalent CVD, occupying the first position as a cause of death worldwide. Studies have shown that polyphenolic compounds have cardioprotective action. Syagrus cocoides Martius, is a palm tree popularly known as coconut ariri, rich in polyphenols. The present study evaluated the cardioprotective potential of the hydroalcoholic extract of S. cocoides almonds (SYA) on cardiac damage caused by isoproterenol (ISO) in an experimental model of myocardial infarction. For this, SYA was obtained, which underwent chemical characterization, determination of total phenols and flavonoids, evaluation of the antioxidant potential using the DPPH elimination method and development of a pharmaceutical formulation (FFL) based on SYA, which was used in the treatment of animals. . The animals were divided into 4 experimental groups: Control (received water), Vehicle (water; 0.01 ml/kg/day), SYA 100 (100 mg/kg/day) and SYA 300 (300 mg/kg/day) , treated by gavage, for 15 consecutive days, in a single daily dose, followed by subcutaneous injections of isoproterenol (ISO; 85 mg/kg) on the 14th and 15th days of treatment for the Vehicle, SYA 100 and SYA 300 groups. On the 16th day electrocardiographic and hemodynamic parameters, estimation of cardiac hypertrophy, determination of the infarction area and serum biochemical parameters of animals subjected to AMI were evaluated. The total phenol content in SYA was 266.38 ± 0.01 mg EAG/g and the flavonoid content was 83.50 ± 1.98 mg EQ/g of extract, associated with a high in vitro antioxidant potential in the elimination of free radicals against DPPH. The chemical characterization of SYA by LC-MS/MS and GC/MS shows that SYA has a great chemical diversity containing alkanes, fatty acids, ethers, amides, ketones and esters, with a high amount of procyanidins. Oral treatment with SYA's FFL reversed the electrocardiographic changes induced by ISO, maintaining blood pressure patterns within normal limits when compared to the Vehicle and Control groups, respectively, suggesting that SYA contains compounds that modulate the cardiovascular system, with actions on the heart rate. Prior treatment with FFL (SYA 100 and SYA 300) significantly reduced myocardial hypertrophy and infarction area promoted by ISO. Corroborating these findings, FFL, in both doses, significantly reduced serum levels of creatine kinase and creatine kinase-MB, lactate dehydrogenase and aspartate aminotransferase, to values comparable to the Control group. Taken together, the results obtained suggest a cardioprotective property for the ariri coconut, generating a patent, thus opening new perspectives for the biotechnological use of the Syagrus cocoides species, expanding the possibilities of applying this species in biological and pharmacological models, especially in treatment and prevention of myocardial infarction.